DAYA SAING KELAPA SAWIT DI KABUPATEN ROKAN HULU - Delwina, Defi; A’ini, Yulfita (E-Journal Sungkai, 2012)
This study aims to determine the Competitiveness of Oil Palm in RokanHulu Regency. Research areas defined intentionally, KuntoDarussalamsubdistrict. Research carried out for 8 months. Allegedly thecompetitiveness of oil palm poepleâs farmers is lower than KKPAâsfarmers.The research method used was a survey method. Method ofsampling was purposive sampling. Samples were taken as many as 30samples from each group for a total sample population used were 60samples. Required data were primary data and secondary data. Thecollected data were analyzed descriptively. Data analysis is productionefficiency approach. Hypothesis were tested using two-sample t-testindependent.The results showed that the efficiency of oil palm poepleâsfarmers is lower than KKPAâs farmers. Chart efficiency patterns ofpoepleâs farmers tend fliktuatif pattern while KKPAâs farmers tendsstable pattern. Based on the t test average efficiency farm of poepleâsfarmers and KKPAâs farmers is significantly different. This shows thatthe competitiveness of oil palm poepleâs farmers is lower than KKPAâsfarmers.